PERSEPSI ORANG TUA PADA PERKEMBANGAN SOSIAL EMOSIONAL TERHADAP ANAK USIA DINI MELALUI PROGRAM PARENTING - Maria Delastrada Bhoki; Gde Putu Arya Oka; Angelina Kurnia Juita; Marsianus Meka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The urgency of this research is to describe in depth the parents' perceptions of the development of the socio-emotional aspects of early childhood in PAUD. The purpose of this study is to provide practical insights to improve parenting programs, supporting children's socio-emotional development. The study, entitled